A Study on Prerequisite Steps and Decision Making to Increase a Provability of Innovation in Mechanical Engineering SMEs - Haruyama, Shigeyuki; Fujiyama, Kojiro; Masuda, Koji (International Journal of Integrated Engineering, 2024)
This study is a case study of two Japanese SMEs, Y and O, that have created core technologies through mechanical engineering, achieved sustainable growth through technological innovation, and achieved niche top company status. Companies need to generate innovation to achieve sustainable growth, and various studies have been conducted on innovation models. It has also been shown that innovation is not a one-off event but a process and that it is important to manage the process appropriately. In this context, we propose a four-stage process, beginning with the "Generating value" step as a framework for the innovation process of a company aiming for sustainable growth. To increase the certainty of innovation, management needs to understand the readiness of the innovation process to determine the decision to execute the process. Accordingly, this study proposed a method to check the readiness of the innovation process by creating a "state diagram of sub-elements for the prospect of generating innovations" to help management determine the decision to execute the process before the "Generating Value" step of the innovation process. In order to confirm the validity of the state diagram, we examined how the management of Company Y's refrigerated vehicle business and Company O's mower business have judged their decision-making to implement the innovation process, based on a review of company documents and interviews with the management. The results of the comparative verification between the state diagrams and actual results are reported